A comparative visual analysis of the architectural elements of ancestral and vernacular houses in Glan, Sarangani Province - Franco, Sheena Marie R.; Orendain, Dan Jezreel (2016)
Architecture has been strong indicator of the cultural identity with in an area whether foreign or domestic. During the American colonial period, settlements in Glan, Sarangani were influence by the colonial body. Up to the present time, ancestral houses still exist and recorded. The design and layout of these houses are believed to be influential in the area leading to the greater possibility of architectural adaptation by the vernacular domestic houses. The historical value of the structure is an essential factor that can influence the nature and characteristics of other structures in the vicinity. This research is done to determine the evolution of historical houses through time thus to evaluate whether these ancestral houses influence the architectural elements of vernacular houses of the most recent years. The study aims to compare the types and styles of the architectural elements in ancestral and vernacular houses using timeline. A comparative visual analysis will determine what among these elements persist over the years to evaluate the relationship of the architectural elements of ancestral and vernacular houses. Based on the results of comparative visual analysis of the architectural elements of both ancestral and vernacular houses through timeline, it can be evaluated that most of the common architectural elements in ancestral houses are also common among the vernacular houses. The persistence of architectural elements is measured through the percentage of frequency distribution in ancestral and vernacular houses. Results show that the most common elements in both houses are also the elements that persist over the years through the use of timeline. Hence, there is an architectural influence from the ancestral to vernacular which is identified in the characteristics of the elements. The research has proven the commonalities among the architectural elements of ancestral and vernacular houses. The relationship between them can be identified as an architectural influence from historical buildings to the local culture of the community. Thus, there is a historical continuity through architecture linking the characteristics of the architectural elements in the colonial past up to the present time. Therefore, the cultural and historical identity of Glan, Sarangani Province and the people is defined.
Thesis (BS Architecture) -- University of the Philippines Mindanao, June 2016.